A study on quality of cost data in Life Cycle Cost analysis of maintenance during the in-use phases of university building - Bidi, Nor Khalisah; Ayob, Mohd Fairullazi; Aripin, Srazali; Mat Noor, Noorsidi Aizuddin (Construction Research Institute of Malaysia (CREAM), 2020)
Life Cycle Cost (LCC) analysis is an economic assessment technique that can help building owners to determine the most optimum total cost of maintaining the building and to compare the most cost-effective of mutually exclusive alternatives by discounting the future cost to today’s value. However, many commentators pointed out that the key setback of implementing LCC technique is the difficulty on identifying and procuring quality and reliable data, which can be used as inputs into the process of producing a complete and reliable LCC analysis. The objective of this paper is to present the outcomes of the study on the quality of cost data as inputs for LCC analysis of maintenance during the in-use phases of university building. The methodology employed for the study is a qualitative research strategy that comprises of literature review and semi-structured interview. The quality of cost data of the operation and maintenance cost of the university building was studied to determine the readiness of the cost data as inputs into the process of producing a comprehensive and reliable LCC analysis of maintenance during the in-use phases for the university building maintenance management practice. The semi-structured interview was carried out with the identified group of people that have knowledge, skills or experience in the field of university building maintenance practice with the objectives to obtain feedback and opinions on the state of data quality, and to identify strategies that can be recommended to improve the quality of data for the practice of LCC analysis of maintenance during the in use-phases of university building. The results have established that the operation and maintenance cost data of the university building are not readily available, accessible, current and reliable to be used as inputs in producing a comprehensive and reliable LCC analysis of maintenance during the in-use phases of university building. To overcome this setback, the majority of the interviewees recommended there is a need to develop an appropriate methodology encompasses with strategies that can improve the quality of data in effort to produce a comprehensive and reliable LCC analysis of maintenance during the in-use phases of university building.